Wealth, Portfolios, and Unemployment Duration - Francois Fontaine; Janne Nyborg Jensen; Rune Majlund Vejlin (Institute of Labor Economics (IZA), 2020)
We use administrative data on individual balance sheets in Denmark to document how an individual's financial position affects job search behavior. We look at the effect of wealth at the entry into unemployment on the exit rate from unemployment as well as the effect on the subsequent match quality. The detailed data allows us not only to distinguish between liquid and illiquid parts, but also to decompose each of them into assets and liabilities. The decomposition of wealth into these four components is key to understanding how wealth affects job finding rates. In particular, we show that liquid assets reduce the probability of becoming re-employed, but we do not see an effect of liquid liabilities or the illiquid wealth components, while interest payments speed up re-employment. The results on subsequent match quality in form of job duration and wages are mixed.
Keywords: J6; J64; J65; 330; non-employment duration; wealth composition; job search behavior